METODE STRUCTURAL EQUATION MODELLING (SEM) UNTUK MENENTUKAN KELAYAKAN PENERIMA PROGRAM KELUARGA HARAPAN (PKH) KECAMATAN MEDAN BARAT - Darma Wogisfry; Rahmawati Pane; Elly Rosmaini; Aghni Syahmarani (MES: Journal of Mathematics Education and Science, 2025)
Structural Equation Modeling (SEM) is a statistical analysis method used to test the relationship between variables in a model. SEM can be used as a statistical technique that takes into account latent and manifest variables, so in this study the SEM method was used to determine the eligibility of PKH recipients in West Medan District. Poverty has become a serious problem that is increasingly being faced by several countries in the world, including Indonesia. The Indonesian government has implemented many programs to overcome poverty, one of which is the Family Hope Program (PKH). Based on the research results, it is known that there is a direct negative relationship (indicating that an increase in one variable tends to decrease another variable), namely the family economic variable on the eligibility of recipients of the Family Hope Program